TEACHERS’ ASSESSMENT OF THE AVAILABILITY AND USE OF INSTRUCTIONAL MATERIALS FOR THE TEACHING OF VOCATIONAL SUBJECTS - Oyebola, Adetayo Janet (Sokoto Educational Review, 2018)
This study was conducted to assess the availability and utilization of instiuctional materials for the teaching o f vocational subjects in secondaiy schools. The study adopted a survey design. A total o f four hundred vocational subjects teachers drawn from two Local Government Areas of Ogun State were used for the study. The results o f the study revealed that most o f the listed instructional materials are not available in schools and where they are available they are not in good conditions. However, the study also revealed that there is a significant difference in the usage o f the available instructional materials according to teachers’ qualifications. The paper however emphasized the need to ensure immediate supply ofnecessaiy teaching facilities into the schools if the aim o f maldng the students self-reliant is to be achieved in the countiy.